Unconditioning Postmodernity: Radical Acts of Resistance in Contemporary Texts - WALTERS, TIMOTHY L. (My University, 2003)
This dissertation investigates several contemporary texts I can subversive defamiliarizations in which charn.cters take extreme measures in order to exist outside of the hegemonic limits of late-capitalist culture. It is my assertion that these texts are different to previous representations of counter-cultural resistance in important ways, precisely because of the wildly unusual methods necessarily adopted by their characters to evade a culture that seems to have become increasingly perverse and pervasive. Chapter 1 contains an introductory definition of subversive defamiliarizations and the specific cultural milieu which they interrogate. Chapter 2 is a consideration of Chuck Palahniuk's novel Fight Club and David Fincher's t1lm adaptation, in which the anarchic protagonist instigates a broad range of extreme acts of resistance in an attempt to place himself ideologically outside of consumer culture. Chapter 3 discusses Irvine Welsh's Trainspotting and Danny Boyle's film version, which argue that the rules of modem existence have become so detrimental to the contemporary subject that even a potentially life threatening alternative lifestyle (heroin addiction) may be more rewarding. Chapter 4 examines Lars von Trier's Dogme95 film The Idiots, about a group of Danes who are united by the bizarre belief that "spassing," or pretending to be mentally retarded, constitutes a genuine critique ot~ and alternative to, late-capitalist life. Chapter 5 concludes this dissertation with a brief analysis of three novels--Chuck Palahniuk's Survivor and Bret Easton Ellis's Glamorama and American Psycho--subversive defamiliarizations that frame their critiques by presenting characters who completely immerse themselves in their culture's ideology. The critical function ofthese texts emerges because, in each case, an escalating surrender to, and absorption by, the dominant culture occurs simultaneously and causally with encroaching madness.
Keywords: English Language and Literature; contemporary texts; late-capitalistic culture